Precisamos falar sobre os fenômenos informacionais contemporâneos no contexto arquivístico: um mapeamento da produção bibliográfica sobre pós-verdade, desinformação e fake news - SANTOS, Maria de Nazaré Coelho dos (2023)
Given the emergence of different information phenomena that negatively affect the appropriation and dissemination of information, there is a need to include such discussions in the context of Archival Science, considering different aspects around the production, maintenance, dissemination and access to archival information and documents and construction and preservation of documentary heritage. Another aspect that must be considered is the recognition of Information Literacy as analternative to minimize the impacts of such phenomena. Thus, this article aims to map the bibliographic production related to the triad Archival Science, Informational Phenomena and Information Literacy, assuming that there is few research that have as object the triad presented here. To achieve the proposed objective, a Systematic Bibliographic Review was developed, whose results indicated the inexistence of research (assuming no synonyms were used for the keywords) addressing the three elements, and only two results that relate Archival Science with the informational phenomena Post-Truth and Fake News. The results confirm the initial assumption indicating the low bibliographic production about the investigated triad. It is expected that this scenario will soon be changed,especially in the Brazilian context, which has been suffering from day to day the impacts of such phenomena that can be perpetuated, compromising the informational quality of the national documentary heritage.